The UNIDO World Productivity Database: An Overview - Anders Isaksson (International Productivity Monitor, 2009)
This article introduces a new unique database, the World Productivity Database (WPD), which contains information on levels and growth of aggregate total factor productivity (TFP) for up to 112 countries, covering the period 1960 to 2000. At its core are numerous measurement methods, variations in functional forms and specifications — including schooling and health — of the production function, constant and variable returns to scale, as well as measures of technical progress and change in technical efficiency. In addition, five labour and four capital stock measures are used to derive a variety of TFP measures. Another significant feature is TFP forecasts for the period of 2001-2010.